Sustainability Marketing Commitment: Empirical Insights About Its Drivers at the Corporate and Functional Level of Marketing - Tollin, Karin (Journal of business ethics, 2019)
Corporate sustainability is an important strategy and value orientation for marketing, but scarce research addresses the organizational drivers and barriers to including it in companies’ marketing strategies and processes. The purpose of this study is to determine levels of commitment to corporate sustainability in marketing, processes associated with sustainability marketing commitment, drivers of sustainability marketing at the functional level of marketing, and its organizational context. Using survey data from 269 managers in marketing, covering a broad range of industries in Sweden and Denmark, we took a structural modelling approach to examine construct relationships, mediation, and moderation effects. Overall, the findings show that marketing capabilities associated with the innovation of new products, services, and business models constitute a strong driver to leverage sustainability marketing commitment. In conjunction with insights into processes related to the enactment of sustainability marketing, this result indicates that companies’ marketing departments have a propensity to drive corporate sustainability. The study provides substance to the idea of aligning substantive marketing capabilities closer to dynamic capabilities. Accordingly, the study reveals that reliance on market orientation alone does not lead to greater sustainability commitment.